A GRASP-based heuristic algorithm for the issue of restricted, Ggillotine two-dimensional cut - Velasco, André Soares; Paula Junior, Geraldo Geraldo de; Neto, Euclydes Vieira (Revista Gestão da Produção Operações e Sistemas, 2008)
This work study a particular case of cutting problems, known in the literature as constrained and guillotinetwo-dimensional cutting problems. The problem consist in determining the best form to obtain a quantity ofrectangles pieces, making cuts like guillotine kinds, in rectangles plates in store. Considering its combinatorialcomplexity and a variety of practical application, this problem is approached by heuristic method. In this workis presented a heuristic formulation based on the GRASP methodology, as proposition to solve the cuttingproblems. In order to presenting the efficiency the heuristic propose it was realized computer tests in instancesfound in the literature.Keywords: Cutting problem; Two-dimensional constrained guillotine cutting patterns; GRASP